Really, Really, Really Easy Step-by-Step Digital Photography. : For Absolute Beginners of All Ages - Hoole, Gavin, 1940- and Smith, Cheryl (London New Holland Publisher, 2006)
Explains the process of picture-taking and sharing digital images. This book covers basic camera usage and guides the reader towards the choice of camera that is appropriate for their skills, needs and budget. It is aimed at users running PCs under Windows XP; the authors make use of a Canon digital camera as a 'generic' model.
Include Color Illustration and Index
Keywords: Photography--Digital techniques -- Image processing--Digital techniques